The Role of Leadership in Improving Legal Understanding in the Indonesian National Armed Forces - Haryadi, Slamet (CV. Strata Persada Academia, 2024)
This study explores the critical role of leadership in enhancing legal understanding within the Indonesian National Armed Forces (TNI). Despite the importance of law enforcement and discipline for TNI's integrity, a gap between legal theory and practice persists. This underscores the need for leadership that instills a robust legal culture within the organization. Using a descriptive-analytical method with a qualitative approach, the study examines the relationship between leadership and legal understanding in the TNI. Data was gathered through document and literature reviews, employing Organization Health Audit (OHA) and Environmental Scanning (ES) to assess legal applications and external influencing factors. The findings reveal that leadership is essential in improving legal understanding and application within the TNI. Leaders who embed legal values into the organizational culture and model compliance effectively foster a consistent law enforcement environment. The study also highlights the need for a meritocratic system in leadership selection to optimize legal application. It recommends strategic steps, including leadership training, improved legal education, enhanced monitoring systems, and increased collaboration with other law enforcement agencies to strengthen legal understanding and compliance, thus reinforcing TNI's professionalism and integrity.